Validation of in vitro labeling method for human use of heat-damage red blood cells to detect splenic tissue and hemocateretic function - Sammartano, Antonino; Scarlattei, Maura; Migliari, Silvia; Baldari, Giorgio; Ruffini, Livia (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Selective imaging of the splenic tissue is obtained with heat-damaged, or heat-denatured, red blood cells (RBCs) of the patient labeled with 99mTc in a variety of clinical scenarios. Aim of the study was to validate the process used for labelling heat-damaged red blood cells “totally in vitro”, after blood sample collection, before re-inject labeled RBCs to the patient. Moreover, we assessed efficacy of the staff training programme in order to guarantee repeatibility and method standardization in the clinical routine. Methods: The validation process of the labeling procedure was performed in three different patients during three consecutive days. After collection of a blood sample using a heparinized syringe, we isolated erythrocytes from other blood components by centrifugation and washing steps. Then, we added the stannous pyrophosphate (PYP) to the erythrocytes pellet, after  pH control. The ‘pretinning’ of RBCs was necessary to reduce Tc-99m once pertechnetate was entered them. After the labeling reaction with 130 MBq of 99mTc-pertechnetate, the erythrocytes were denatured in a water bath at a temperature of 49°-50°C, for 10 min. Radioactivity of blood aliquotes was measured with a dose calibrator and labelling efficiency (LE%) was determined. The labelling purity was measured using a gamma counter  and calculated using the formula: counts of pellet/counts of pellet+(counts of surnatant)*100.Training program was evaluated using a Learning Questionnaire (LQ). with a grading score from 6 (“”) to 1 (“nothing”) for each operator (n=3). Results: We didn’t observed the presence of macroaggregates during the entire process, until the final sample. The labelling efficiency resulted at very high values in the three consecutive measured aliquotes (mean value 73.67%) as well as the labelling purity (>95.22%). In our instituion, we use splenic imaging with labelled heat-damaged RBCs to detect ectopic spleen, splenosis, extramedullary hematopoiesis. We performed 3 procedures with  heat-damaged labeled RBCs with a  mean labelling efficiency 73.67%.Training and learning programmes were scored by key objective areas with a mean value of 5. Conclusions: Our in vitro labeling process of heat-damaged RBCs is simple and safe, providing a useful technique  easy to implement in clinical routine for splenic imaging Learning outcome of the training programme was scored as effective by all the operators with evidence of high-efficiency-reproducible procedure mantained over time.